THE IMPORTANCE OF THE PREHOSPITAL STAGE FOR THE DIAGNOSIS AND TREATMENT OF DIABETIC FOOT SYNDROME - Abdurakhmanov, F.M. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. The rapid course of diabetes mellitus, the rapid progression of its complications, and the high percentage of amputations of the lower extremities make diabetic foot syndrome the most important medical and socio-economic problem. All the above allows us to consider the problems considered in this study to be very relevant for clinical medicine. Material. We examined 255 patients with type 1 and type 2 diabetes mellitus (22 (8.6%) and 233 (91.4%) patients, respectively), the duration of which ranged from 5 to 25 years. Among the patients, there were 58 (22.7%) men and 197 (77.3%) women, their average age was 59.3 years. Conclusion. The application of the proposed algorithm for diagnosing diabetic foot syndrome at the outpatient level will reduce the number of amputations of the lower extremities, reduce the number of validations and the high mortality of patients. The use of alpha-lipoic acid preparations is more appropriate in the earlier stages of the development of diabetic neuropathy when reversible processes in the nerves are still possible.